Spectrophotometric Determination of some Drugs using Oxidation Reduction Reactions - Saleem, Basima A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
A spectrophotometric method is proposed for the determination of some drugs containing amino group such as mesalazine, metoclopramide and dopamine in pharmaceutical formulations. It was simple, precise, accurate, rapid, and based on the oxidation of each drug with chromate as an oxidizing agent in the presence of 1N hydrochloric acid. Then indigo carmine is reacted with residual chromate in the presence of a catalysis factor (sodium oxalate). Increasing in absorbance's value of the color system is proportional to the amount of the three drugs which is measured at the selected wavelength of 610 nm.The proposed method is obeying Beer's law in the ranges of (1-40, 2-44 and 2-52) ppm for the concentration of mesalazine, metoclopramide and dopamine respectively. Molar absorptivity was 0.191×104, 0.449×104 and 0.191×104 L.mol-1.cm-1 mesalazine, metoclopramide and dopamine respectively. While, Sandell's sensitivity index of 0.0806, 0.0667 and 0.0806 μg.cm-2 mesalazine, metoclopramide and dopamine respectively.The proposed spectrophotometric method has a good recovery when it is applied for the determination of the three drugs in pure form and pharmaceutical doses.